2010
DOI: 10.1002/ajh.21885
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow reticulin and collagen content in patients with adult chronic immune thrombocytopenic purpura: A Danish nationwide study

Abstract: We quantified and differentiated reticulin and collagen content in bone marrow specimens from chronic immune thrombocytopenic (ITP) patients and examined the correlation between some clinical characteristics and the fibrosis grading. Through the Danish National Patient Registry, we identified 378 patients with chronic ITP from 1997 until 2007. Of these, 253 (67%) had undergone at least one bone marrow biopsy, and we retrieved the bone marrow specimens from 187 (74%). We graded the bone marrow content of reticu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 18 publications
2
14
0
Order By: Relevance
“…Recently, another study addressed specifically the issue of marrow fibrosis in a large population of primary immune thrombocytopenia patients never treated with thrombopoietin receptor agonists; patients with primary immune thrombocytopenia were showed to have a comparable degree and incidence of marrow fibrosis to that found in healthy individuals. 25 In this study, we observed a slight but significant increase in reticulin fibres in half of our cases, with four of eight patients showing a one degree increase, from MF-0 to MF-1 after the initiation of therapy with thrombopoietin receptor agonists. These results are comparable to those seen by Kuter et al 13 and seem to support the hypothesis that thrombopoietin receptor agonists can induce mild reticulin fibrosis.…”
Section: Discussionsupporting
confidence: 48%
“…Recently, another study addressed specifically the issue of marrow fibrosis in a large population of primary immune thrombocytopenia patients never treated with thrombopoietin receptor agonists; patients with primary immune thrombocytopenia were showed to have a comparable degree and incidence of marrow fibrosis to that found in healthy individuals. 25 In this study, we observed a slight but significant increase in reticulin fibres in half of our cases, with four of eight patients showing a one degree increase, from MF-0 to MF-1 after the initiation of therapy with thrombopoietin receptor agonists. These results are comparable to those seen by Kuter et al 13 and seem to support the hypothesis that thrombopoietin receptor agonists can induce mild reticulin fibrosis.…”
Section: Discussionsupporting
confidence: 48%
“…For example, in a nationwide population-based retrospective study of patients with cITP receiving various therapies, but not TPO-RAs, 40% had increased BM fibrosis (MF-1 in 38.5% and MF-2 or MF-3 in 1.6%) [11]. Furthermore, increased BM reticulin has been described in patients with other autoimmune diseases [12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…Whether the risk of BM fibrosis is due to the TPO-RAs themselves or the underlying disease remains unclear. Even in the absence of TPO-RAs, the results of several studies have revealed the presence of background BM reticulin fibrosis in patients with a diagnosis of ITP [6,11,18,19,20]. Furthermore, increased BM reticulin formation has been described in patients with refractory ITP, as well as in those with other autoimmune diseases [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies have retrospectively reviewed biopsy specimens, prospectively collected data in patients with chronic ITP are limited. A Danish study of 187 patients with chronic ITP never treated with TPO-RAs showed that 60% had MF-0, 39% had MF-1, and approximately 2% had MF-2 or MF-3 [18]. Whether the risk of BM fibrosis is due to the TPO-RAs themselves or the underlying disease remains unclear.…”
Section: Discussionmentioning
confidence: 99%